2012
DOI: 10.4103/0972-9941.103110
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic adrenalectomy for large tumours: Single team experience

Abstract: BACKGROUND:Laparoscopic adrenalectomy (LA) has become the procedure of choice to treat benign functioning and non-functioning adrenal tumours. With improving experience, large adrenal tumours (> 5 cm) are being successfully tackled by laparoscopy. This study aims to present our single unit experience of LA performed for large adrenal masses.MATERIALS AND METHODS:Forty-six laparoscopic adrenalectomies performed for large adrenal lesions more than 5 cm during the period 2001 to 2010 were reviewed.RESULTS:A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Some authors consider a diameter of ≥6 cm a relative contraindication to laparoscopic adrenalectomy [3,4]. On the other hand, there are recent publications where authors report the feasibility of laparoscopic adrenalectomy of large tumors [15,16,17,18,19,20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors consider a diameter of ≥6 cm a relative contraindication to laparoscopic adrenalectomy [3,4]. On the other hand, there are recent publications where authors report the feasibility of laparoscopic adrenalectomy of large tumors [15,16,17,18,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are reports of high rate of intraoperative complications [14]. However, tumor size as a limitation for laparoscopic adrenalectomy is questioned by some authors [15,16,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…The average operative time, estimated blood loss, perirenal drainage time, postoperative hospital stay, postoperative drainage, and transfusion rate were 176.3 ± 49.7 min, 247.2 ± 274.1 mL, 4.1 ± 1.02 days, 6.3 ± 1.4 days, 73.6 ± 47.9 mL, and 1/18, respectively. Compared with those in a previous study in which patients with large adrenal tumors (8 cm) underwent LTA, the operative time and hospitalization time were longer and the blood loss was greater, but complications such as conversion to OA and blood transfusion were reduced (Table ) . Moreover, Insang et al evaluated the surgical feasibility of RLA for tumors ≧5 cm and found that the operative time, estimated blood loss, postoperative hospital stay, transfusion, and surgical complications were 214.54 ± 76.04 min, 367.24 ± 275.11 mL, 9.26 ± 3.10 d, 6 (7.9%), and 13 (17.1%) respectively, for large adrenal tumors (7.10 ± 2.15 cm) (Table ) .…”
Section: Discussionmentioning
confidence: 66%
“…However, RLA may pose serious additional technical difficulties, such as a smaller working space, poor surgical landmarks, a steeper learning curve, and discomfort when working with tumors larger than 8 cm . As the size of the adrenal tumor increases, the surrounding anatomy is disturbed; the tumor tends to exhibit local invasion with intense adhesions to periadrenal structures, the vessels in the tumor vicinity become more dilated, and there is a greater number of intraoperative hemodynamic events in pheochromocytomas . Therefore, adrenal masses >8 cm are technically more difficult to remove, because the tumor limits manipulation with devices and obstructs the operative field.…”
Section: Discussionmentioning
confidence: 99%
“…Since the improvement of laparoscopic instruments and proficiency of operation skill, the tumor diameter may not be the major restricting factor 32 . While, there were discrepant opinions on the application of laparoscope in the management of large (> 5cm) adrenal tumor 33,34 . The aim of the present study was to compare the results of LRA and OA in the management of large adrenal tumors (> 5cm).…”
mentioning
confidence: 99%